Network behavior as a specific feature of generation Z communicative competence and their readiness for online learning - Irina Tolstikova; Olga Ignatjeva; Konstantin Kondratenko; Alexander Pletnev (Journal on Interactive Systems, 2023)
The article presents the results of a longitudinal study of young people belonging to the category of generation Z. The study was conducted over a period of 3 years, starting in 2019, and was devoted to studying the formation of social characteristics of generation Z under the influence of socialization in the digital environment. The study also included a comparative analysis of the younger and older age groups in Generation Z, who are now high school students and students. The results of the study showed that the younger representatives of generation Z have a more pronounced desire for individualism and self-organization on the Internet. The social characteristics of generation Z must be taken into account when organizing online learning.